Assessing the impact of the SASA/CASREN technology interventions in the sweet potato-pig production systems in Zitong County (Sichuan, China) - Pezo, Danilo A. (International Livestock Research Institute, 2004)
The present paper describes the processes applied by the Sichuan Animal Science Academy (SASA)/CASREN Team in Zitong County in order to improve the sweet potato-based pig production systems that are predominantly present in that area, which is representative of the rainfed uplands of Sichuan Province (China). The methodology applied by the CASREN project to scale up promising technology interventions in croplivestock systems is described. Some of the differences between the work in the benchmark site in Sichuan Province and other CASREN sites is also briefly described. The last part of the report contains a detailed description of the basket of technology op tions proposed by the SASA/CASREN Team, as well as some of the findings in the preliminary assessment of their impact. The technologies included in the basket of options are: improved sweet potato varieties (high yielding, starch-rich); conservation of sweet potato roots and vines as silages as a means to increase the efficiency of utilisation of sweet potatoes as animal feed; use of a premix or a protein-rich concentrate to supplement sweet potato-based diets; upgrading the local pig genotypes using improved breeds; implementation of a simple preventive disease control program; and improved housing. The report contains some of the preliminary results obtained applying a set of criteria for assessing the impacts at the plot and household level, after applying the technology interventions as proposed by the SASA/CASREN Team. Among those criteria are: increased sweet potato yield; larger area planted to the improved varieties; reduction of losses due spoilage when sweet potato roots and vines are ensiled; savings in fuel when silages are prepared instead of offering fresh roots; shorten the growing/fattening period; increased numbers of pigs marketed; increased income from pig; reduced costs of feeding; faster capital turnover in the pig enterprise; and final ly improved livelihood for household members. At the end of the report there is a brief section on institutional impacts.